Conservation de l’énergie et maillages évolutifs en dynamique: Application aux calculs de propagation de ssure avec remaillage - Réthoré, Julien; Gravouil, Anthony; Combescure, Alain (European Journal of Computational Mechanics, 2004)
This paper presents a general study of the stability of variable-mesh dynamic calculations using an energy approach. This study, whose scope is limited to the calculation of dynamic crack propagation with remeshing, enables us to establish the conditions which are necessary to ensure stability and allow control of energy transfers during the evolution of the mesh. The results obtained on an sample problem are analyzed to illustrate the effectiveness of the proposed methods.